Pengembangan model manajemen Open Educational Resources (OER) Perpustakaan Institut Agama Islam Negeri Curup - Rahmat Iswanto; Jurianto Jurianto (Jurnal Kajian Informasi dan Perpustakaan, 2020)
Open education resources (OER) are an interesting and diverse source of information that is easily accessible. For the Institut Agama Islam Negeri (IAIN) Curup library, the OER is an alternative service to meet visitors' needs through resources offered are so diverse that it needs adjustment and development. This study was conducted to find out development an effective OER management model to meet IAIN Curup library users' needs. This research used a combination of qualitative and quantitative research types. This study used a research and development method, adoption of the Borg and Gall model. Results showed that the OER management model was selected and developed by testing users' and experts' needs and opinions following the IAIN. OER management model comprised four stages. Stage 1 planning, consisting of steps needs analysis, identification, and verification or preparation.  Stage 2 of organizing namely processing activities. Stage 3 actualizing, which consisted of steps service, and promotion. Stage 4 was evaluation. The (OER) management model application was useful. The IAIN Library's OER application could be accessed via a browser at the address http://oer.iaincurup.ac.id; with this open-source platform, and each library could add specific features such as search features, usage statistics, and others. The study concludes that the development of an OER management model for the IAIN Library Curup is still essential so that effectiveness of library services is following the conditions of the community's needs.